2018
DOI: 10.1177/0894439318814241
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Self-Report and Trace Data Measures of Incivility: A Proof of Concept

Abstract: This study correlated self-report and trace data measures of political incivility. Specifically, we asked respondents to provide estimates of the degree to which they engage in uncivil political communication online. These estimates were then compared to computational measures of uncivil social media discussion behavior. The results indicated that those who self-disclose uncivil online behavior also tend to generate content on social media that is uncivil as identified by Google’s Perspective application progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…In both cases, threatening language is affectively negative in nature and employed for the purposes of designating the target as malignant and, thus, worthy derision. This dimension addresses the interpersonal threat component included in Massaro and Stryker (2012), Santana (2014), and Hopp et al (2018), and the threat to democracy dimension found in Rowe (2015). Consistent with prior renderings of incivility in Coe et al (2014), Gervais’ (2014, 2015b), Sobieraj and Berry (2011), and Stryker, Conway, and Danielson (2014), the persuasive deception dimension refers specifically to purposeful lying or weaponized use of ambiguity.…”
Section: A Theoretical Rendering Of Online Political Incivilitymentioning
confidence: 77%
See 3 more Smart Citations
“…In both cases, threatening language is affectively negative in nature and employed for the purposes of designating the target as malignant and, thus, worthy derision. This dimension addresses the interpersonal threat component included in Massaro and Stryker (2012), Santana (2014), and Hopp et al (2018), and the threat to democracy dimension found in Rowe (2015). Consistent with prior renderings of incivility in Coe et al (2014), Gervais’ (2014, 2015b), Sobieraj and Berry (2011), and Stryker, Conway, and Danielson (2014), the persuasive deception dimension refers specifically to purposeful lying or weaponized use of ambiguity.…”
Section: A Theoretical Rendering Of Online Political Incivilitymentioning
confidence: 77%
“…Despite its potentially deleterious effects on democratic functioning, scholars have yet to settle upon a consistent definition of political incivility (Hopp et al, 2018; Stryker, Conway, & Danielson, 2014; Su et al, 2018). Building upon a synthesis of prior work, however, it is here suggested that incivility attributes can be segmented into two categories, both of which deal with purposeful normative violations.…”
Section: A Theoretical Rendering Of Online Political Incivilitymentioning
confidence: 99%
See 2 more Smart Citations
“…When researchers want to analyze the substance of human communication and behavior, they very quickly face constraints due to the sheer size and unstructured nature of the data, which makes hand-coding unfeasible in most cases (but see Haenschen, 2019). The paper by Hopp, Vargo, Dixon, and Thain (2018) in this issue stands out by applying the Google's Perspective API to classify incivility at a larger scale. The authors demonstrate that there is a considerable congruence between self-reports on online incivility and computational measures.…”
Section: Measurements Constructed From Digital Trace Datamentioning
confidence: 99%